2020
DOI: 10.3390/molecules25040787
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Total Phenolic and Flavonoid Contents of Defatted Pitaya (Hylocereus polyrhizus) Seed Extract and Its Antioxidant Properties

Abstract: The present study was conducted to optimize extraction process for defatted pitaya seed extract (DPSE) adopting response surface methodology (RSM). A five-level central composite design was used to optimize total phenolic content (TPC), total flavonoid content (TFC), ferric reducing antioxidant power (FRAP), and 2,2′-azino-bis (3-ethylbenzothizoline-6-sulfonic acid (ABTS) activities. The independent variables included extraction time (30–60 min), extraction temperature (40–80 °C) and ethanol concentration (60%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 62 publications
2
20
0
4
Order By: Relevance
“…Total flavonoid content was measured by colorimetric analysis [ 22 , 23 ]. To a 15-mL test tube containing 4 mL of distilled water and 1 mL of blueberry extract, we added 0.3 mL of 5% NaNO 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total flavonoid content was measured by colorimetric analysis [ 22 , 23 ]. To a 15-mL test tube containing 4 mL of distilled water and 1 mL of blueberry extract, we added 0.3 mL of 5% NaNO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Total phenolic content was measured using the Folin–Ciocalteu colorimetric method [ 22 , 24 ]. After adding 0.2 mL of blueberry extract to a 15-mL test tube containing 2.6 mL of deionized water, 0.2 mL of Folin–Ciocalteu reagent was added and the mixture was vortexed and left at room temperature for 6 min.…”
Section: Methodsmentioning
confidence: 99%
“…RSM has been widely used in several fields, such as industrial crops and products [ 36 ], food chemistry [ 29 ], and renewable energy [ 37 , 38 ]. Previous studies have shown that RSM was useful in establishing optimal conditions for the extraction of antioxidant compounds and their activities [ 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…In another research that was conducted to optimize extraction conditions for higher total phenolic flavonoids recovery and to determine in vitro antioxidant activities of defatted H. polyrhizus seed extract (DPSE) using response surface methodology, UPLC-QTOF/ MS analysis revealed the presence of rutin at the retention time 8.38 and m/z peak 609.14 which is in a good agreement with the findings of this study. Besides, sinapic acid and flavonoid compounds with core moieties of kaempferol as well as isorhamnetin were also detected in DPSE [53]. e phytochemical composition of HPPE revealed in this study also justifies the good results obtained for its total phenolic content (172.01 mg gallic acid equivalent (GAE)/g) and total flavonoid content (7.45 mg quercetin equivalents (QE)/g) that were conducted in our previous work which focused on optimizing the extraction conditions for phenolic and flavonoid compounds from H. polyrhizus peels using a statistical approach [28].…”
Section: Ultra-high-performance Liquid Chromatography-mentioning
confidence: 98%